Модели управления энергетической системой - Журбенко, Н.Г.; Чумаков, Б.М. (Теорія оптимальних рішень, 2007)
The paper outlines two mathematical models of power system control, namely – a variant model and a model of short-term planning . The proposed methods for solution are based on the use of nonsmooth optimization algorithms.